The political interests of gender revisited : redoing theory and research with a feminist face - Anna G. Jónasdóttir; Jones, Kathleen B., 1949- (United Nations University Press, 2009)
This collection of theoretical and empirical research on gender and politics assembles contributions from a group of international scholars providing varied accounts of the political interests of gender. It examines how to bridge the gap between discursive and socio-materialist accounts of gender relations and politics. Offering new models for theoretical and empirical research, the first five chapters provide a theoretical framework for the collection, while the following eight chapters shed light on key concepts through detailed case studies of such topics as human rights, womens movements, gendered labor markets, international monetary policy, equality policy, and queer politics.--Publisher's description.